Pour une approche génétique de l'ébauche - Floriane Philippe (Les Cahiers de l'École du Louvre)
The terms “ébauche” and “esquisse” occupy a central place in the French artistic lexicon. However, their use is surrounded by a certain amount of confusion : their meaning remains unclear, and they are often treated as synonyms, even by art historians and museum professionals. This article proposes a lexical and material study of the “ébauche” establishing the bases for a working definition for art historians. It examines the causes of the confusion, distinguishing a technical use of the term from an aesthetic or metaphorical one. How and under what conditions can the “ébauche” become an object of study for art history ? Only a genetic approach, centred on the creative processes, allows a precise comprehension of the phenomenon of the “ébauche”.